Effect of Indole Butyric Acid Concentrations on Rooting of Green and Soft Wood Cuttings of Mahaleb SL-64 - Ozkan, Yakup; Madakbas, S.Y.; Gercekcioglu, R.; Gunes, M. (Asian Journal of Chemistry, 2016)
The effect of various rates of indole butyric acid (IBA) on rooting, callusing, number of roots per cutting, length of roots per cutting, number of cuttings remaining active, part forming of roots, number of cuttings usable for producing the plant and root quality of green and soft-wood cuttings obtained from Mahaleb SL-64 was investigated. The cuttings were planted in mist unit, filled with perlite and placed in a high plastic tunnel. The green cuttings were separated into two parts, the bottom and upper cuttings, in June and July of 1995. According to trial results, the highest rooting ratio was found from the green cuttings obtained in June. The hormone concentration 2000 ppm at the upper cutting and 4000 ppm at the bottom cuttings was seen to be more effectual on the rooting. In the upper and bottom cuttings collected in June the average rooting ratio was obtained to be 85.33 and 84.17% respectively. Also for other characteristics examined, the green cuttings are superior.